Seven endless forests - Tucholke, April Genevieve (Farrar, Straus & Giroux, 2020)
In this stand-alone companion novel to The Boneless Mercies, the Cut-Queen and her band of shaven-skulled witches, The Hounds, are using their dark magic in an attempt to kill or convert everyone in Vorseland. Well, almost everyone. Seventeen-year-old Torvi and her younger sister, Frigga, are still fighting for goodness and light in a land covered in snow. But when the Cut-Queen captures Frigga, Torvi teams up with a band of new characters to rescue her sister or die trying. In this gender-bent retelling of King Arthur, April Tucholke showcases more fierce girl heroes, bloodlust, and quests for power in another darkly elegant tale that is perfect for fans of Maggie Stiefvater, V.E. Schwab, and Heidi Heilig.